Aurantii fructus immaturus carbonisata-derived carbon dots and their anti-depression effect - Li, Xiaopeng; Dai, Ertong; Li, Menghan; Kong, Ruolan; Yuan, Jinye; Li, Tingjie; Wang, Shuxian; Zhang, Yue; Kong, Hui; Zhao, Yan (Frontiers in Molecular Biosciences, 2024)
Introduction: Depression is a common illness worldwide. However, the current treatments available for depression only achieve relative success, often come with several side effects, and are associated with high costs. Aurantii Fructus Immaturus (AFI) has a rich historical legacy in Traditional Chinese Medicine (TCM) for its traditional use as a treatment for depression. In this research, our primary objective is to examine the potential antidepressant properties and the mechanisms at play behind a particular bioactive compound found in AFI, which is referred to as carbon dots derived from AFI Carbonisata (AFIC-CDs).Methods: Extracted and isolated the AFIC-CDs from the decoction of AFIC, then characterized the morphological structure and functional groups comprehensively. We then utilized two distinct models to investigate the anti-depressive properties of AFIC-CDs: the chronic unpredictable mild stress (CUMS) model and the reserpine-induced pain-depression dyad model. In the CUMS model, we assessed immobile time and measured neurotransmitter levels in the mouse brain cortex. In the paindepression dyad model, we evaluated immobile time, neurotransmitter levels, interleukin-1 (IL-1β) and tumor necrosis factor-α (TNF-α) levels, and the expression of mRNA of brain-derived neurotrophic factor (BDNF) and tryptophan hydroxylase 2 (Tph2).Results: AFIC-CDs were found to have abundant chemical groups, and their diameter ranged from 2 to 10 nm. In the CUMS model, AFIC-CDs demonstrated significant effects. They reduced the immobile time of the mice and increased the levels of serotonin (5-HT), dopamine (DA), and norepinephrine (NE) in the mouse brain cortex. In the pain-depression dyad model, the AFIC-CDs groups decreased the immobile time, showed effect in increasing both the neurotransmitters' levels and the expression of mRNA of BDNF and Tph2, and decreased the IL-1β and TNF-α levels in mouse brain cortex. Taken together, these results strongly indicate that AFIC-CDs possess significant antidepressant activity.AFIC-CDs demonstrate promising therapeutic potential in the treatment of depression, suggesting that they may become a valuable candidate for depression management. This not only This is a provisional file, not the final typeset article extends the understanding of the biological activity of carbon dots (CDs) but also opens up new possibilities for the development of effective depression treatment strategies.